HIGH EFFICIENCY PUBLIC TRANSPORTATION SYSTEM: ROLE OF BIG DATA IN MAKING RECOMMENDATIONS - Sazu, Mesbaul Haque; Jahan, Sakila Akter (Journal of process management and new technologies, 2022)
Big data has a huge impact on urban planning and cities morphology. Big data is utilized to appraise the requirements of the shared transport structure, by focusing on funding and portability plans inside the key cities. The research provides a recommendation-making system (RMS) focused on suggesting transport methods to automobile consumption by detailing a huge volume of transport methods information originating from various products. The research focuses on the utilization of big data to come down with shared transport, and presents a structural understanding for gathering, combining, aggregating, incorporating, disseminating, and controlling information from numerous origins. Information extraction methods are utilized, allowing the evaluation of both organized big data, that follows developed benchmarks like CRISP-DM, and disorganized, readily offered big data. Investigational information has been gathered from a representative of phones and automatic vehicle location devices in the region. The suggested RMS allowed to examine the temporal and spatial scope of shared transport facilities, and suggested plans to enhance the transportation.